2018
DOI: 10.1111/trf.14789
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of bacterial culture–positive and septic transfusion reactions at a large tertiary academic center: 2009 to 2016

Abstract: BCPTRs are rare yet potentially serious. The signs and symptoms of BCPTRs, and associated STRs, are not specific, posing risk of misclassification. Challenges surrounding reporting and case ascertainment underscore the need for laboratory measures to address residual risk of contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…11 It is widely accepted that passive surveillance PLT cultures drawn early in storage (ie, prior to release from the blood center) is an important, but ultimately inadequate, mitigation strategy for the threat posed by bacteria in PLT concentrates. [13][14][15] The incidence of bacterially contaminated PLTs was reported to be 1 in 2881 at a large hospital blood bank that inoculated cultures from PLTs at the time of receipt (day 3 or 4). 15 Various strategies have been proposed to enhance the sensitivity of PLT cultures, including additional culture time points and larger sampling volumes.…”
mentioning
confidence: 99%
“…11 It is widely accepted that passive surveillance PLT cultures drawn early in storage (ie, prior to release from the blood center) is an important, but ultimately inadequate, mitigation strategy for the threat posed by bacteria in PLT concentrates. [13][14][15] The incidence of bacterially contaminated PLTs was reported to be 1 in 2881 at a large hospital blood bank that inoculated cultures from PLTs at the time of receipt (day 3 or 4). 15 Various strategies have been proposed to enhance the sensitivity of PLT cultures, including additional culture time points and larger sampling volumes.…”
mentioning
confidence: 99%
“…Transfusion of contaminated PLTs would result in no clinical consequences in the majority (75%) of cases . Of those clinical consequences, 44.4% would be minor and 55.6% would be serious . In this model, “serious” complications included severe, life‐threatening, or fatal reactions, as defined using the Centers for Disease Control and Prevention's National Healthcare Safety Network hemovigilance criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The relative probabilities of these consequences were drawn from active surveillance data of bacterially contaminated PLTs over a 7-year period and a retrospective analysis characterizing culture-positive and septic transfusion reactions at a tertiary academic medical center. 23,24 Because it has been suggested that the overwhelming majority of septic reactions occur from contaminated units transfused on Day 4 or later, the analysis assumed contaminated units transfused on Day 3 were less likely to cause serious complications than contaminated units transfused after Day 3. 1,13,25,26 It was assumed that the processes and costs associated with transfusion would not differ across strategies.…”
Section: Model Structurementioning
confidence: 99%
See 2 more Smart Citations